Black and White - Massimo Cacciari (Studies in 20th & 21st Century Literature, 1987)
Black and White
Keywords: De Migrationi Abrahami; Filone; Jew; Jewish; sign; migration; migrant; God; Abraham; Edmond Jabès; identity; self; earth-mother; language; interpretation